Purification of Used Cooking Oil with Avocado Seed Powder as Biosorbent - Iryani, Ani; Hasanah, Retna; Kusumawardani, Linda Jati; Fathurrahman, Muhammad (Jurnal Kartika Kimia, 2025)
Cooking oil is a basic ingredient in food preparation. Repeated use of cooking oil at high temperatures produces free fatty acids (FFA), which indicate oil degradation. The initial free fatty acid content of the used cooking oil in this study was 0.95%. This study aimed to prepare, activate, and evaluate avocado seed powder as a biosorbent for reducing free fatty acids in used cooking oil and to determine the optimal adsorption conditions with respect to temperature, contact time, and adsorbent mass. The activated avocado seed biosorbent showed a moisture content of 5.40%, ash content of 0.68%, iodine adsorption capacity of 768 mg/g, methylene blue adsorption capacity of 22.57 mg/g, and a surface area of 84.69 m²/g. The optimum adsorption condition was achieved at 90°C, 120 minutes contact time, and 20 g adsorbent mass. Under these conditions, the free fatty acid content decreased from 0.95% to 0.40%, corresponding to a reduction in efficiency of 58.05%. The peroxide value and water content were also reduced significantly. The adsorption capacity of avocado seed biosorbent was 27.96 mg/g for free fatty acids, 3.28 mg/g for peroxide value, and 6.16 mg/g for water content.